2003
DOI: 10.1007/s00455-002-0088-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cerebellum and Basal Ganglia on Volitional Swallowing Detected by Functional Magnetic Resonance Imaging

Abstract: Although regions of the sensorimotor cortex, insula, and anterior cingulate gyrus are reported to be activated during swallowing, findings concerning contributions of the cerebellum and basal ganglia have been contradictory. We investigated cerebellar and basal ganglionic activation using functional magnetic resonance imaging (fMRI). In 11 subjects, single-shot gradient-echo echoplanar image volumes sensitive to BOLD contrast were acquired in block design fashion using an oblique orientation covering both cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 19 publications
11
134
0
6
Order By: Relevance
“…Fourteen articles that used fMRI in healthy adults while swallowing were relevant and are detailed in Table 1 [ 41,[53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen articles that used fMRI in healthy adults while swallowing were relevant and are detailed in Table 1 [ 41,[53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
“…However, the rest condition is often implied in fMRI studies. On the other hand, other studies clearly indicated that an "off" swallow [64] …”
Section: Tasksmentioning
confidence: 97%
See 3 more Smart Citations